The Security Issues Barrier Of E-Commerce In Malaysia: Malaysian Consumer Confidence In Using Credit Card Over The Internet - A. Rashid, Tajuddin (2004)
This research will investigate factors such as consumers concern on credit card numbers, privacy, spy wares, cyber crime and consumer liability with regards to online credit card frauds. This thesis will also explores the technology aspect of e-payment, the Cyber law that provides legal protection for transaction over the Internet, the media's role and the Malaysian awareness on Cyber Law and Internet payment technology.